Does an increase in the cost of imported inputs hurt exports? Evidence from firms' network of foreign suppliers - Camara, Santiago (2022)
This paper examines the relationship between changes in the cost of imported inputs and export performance using a novel dataset from Argentina which identifies domestic firms' network of foreign suppliers. To guide my empirical strategy, I construct a heterogeneous firm model subject to quality choice and frictions in the market for foreign supplier. The model predicts that the impact of an increase in the cost of imported inputs to be increasing in the adjustments costs of supplier linkages and in the quality of the product exported. I take the model to the data by constructing firm-specific shocks using a shift-share analysis which exploits firms' lagged exposure to foreign suppliers and finely defined import price shifts. Evidence suggests the presence of significant adjustment cost in firms' foreign supplier linkages and strong complementarities between imported inputs and export performance, particularly of high-quality products.